Klebsiella pneumoniae in stranded California sea lions (Zalophus californianus) of Central California between 2017-2022 - Sydney N. Zotto; Robin C. Dunkin; Juliana D. Limon; Maia S. Smith; Lisabet M. Hortensius; Margaret E. Martinez; Pádraig J. Duignan; Cara Field; Esteban Soto; Dane Whitaker; Carlos Rios; Maurice Byukusenge; et al. (Frontiers in Marine Science, 2025)
Klebsiella pneumoniae is a Gram-negative, facultative anaerobic, and non-motile bacillus frequently observed in mammals. A hypermucoviscous (HMV) phenotype of K. pneumoniae is reported in stranded California sea lions (CSL) causing pleuritis and bronchopneumonia as a persistent cause of strandings. We describe an increase in cases of HMV and non-HMV K. pneumoniae in stranded CSLs along the California coast between 2017 to 2022. 2,146 live-stranded CSLs were rescued by The Marine Mammal Center (Sausalito, California). 47 of these tested positive for K. pneumoniae , with a rise in annual incidence from 0.92% (3/331) in 2017 to 8.5% (14/165) and 7.2% (23/320) in 2021 and 2022, respectively. These strandings occurred across 965 kilometers along the North-Central California coast from Bodega Bay, Sonoma, to Avila Beach, San Luis Obispo. A similar pattern was observed in beach-cast CSL carcasses by the Long Marine Laboratory (LML) Stranding Network in Santa Cruz, California who had 8 CSLs test positive for K. pneumoniae with an annual incidence rate of 2.0% (1/50) and 10.1% (7/69) in 2021 and 2022, respectively, with no cases reported prior to 2021. We applied whole-genome sequencing (WGS) to 8 isolates obtained by LML in 2022. WGS analysis revealed high nucleotide similarity between any pair of isolates. Multilocus Sequence Typing showed that all isolates belonged to Sequence type 65 and contained the K2 polysaccharide capsule and siderophore aerobactin, which are all characteristics of hypervirulent K. pneumoniae. We discuss possible causes for this trend and a need for research on K. pneumoniae in free-ranging CSLs in California.